USING DEXMEDETOMIDINE FOR THE RELIEF OF PAIN IN THE POSTOPERATIVE PERIOD AFTER SPINAL INJURY - Iskenderov, J.N.; Nasibova, E.M. (World of Medicine and Biology, 2023)
Pain syndrome in spinal surgery is an urgent problem far from a final solution. After extensive surgical interventions on the spine, a pronounced postoperative pain syndrome is observed, comparable in intensity to pain after thoracic operations, limb amputations, and extensive interventions on the hip joint. Expansion of knowledge about the pathogenesis of pain formation has led to a revival of interest in the use of drugs such as antidepressants, glucocorticoids, magnesium sulfate, dexmedetomidine for postoperative analgesia. However, data on the effectiveness of their use in spinal trauma surgery are extremely limited. We used dexmedetomidine to optimize perioperative pain management in patients with spinal cord injuries.The study was conducted in the surgical clinic of the AMU. The study included 59 patients who underwent decompression and fixation of the spine at the lumbar and thoracic levels due to spinal cord injury. The patients were divided into 2 groups. In patients of group I, surgical interventions were performed only under general anesthesia, and in group II, dexmedetomidine was included in the general anesthesia regimen. The use of multimodal analgesia protocols, including dexmedetomidine and general anesthesia after decompression of neural structures and fixation of the spine in patients with spinal cord injury, provides adequate pain control throughout the entire postoperative period. In patients operated on for spinal canal stenosis, the use of this scheme does not provide adequate pain control only during the first two hours after surgery.